Common dietary patterns and risk of cancers of the colon and rectum: Analysis from the United Kingdom Women's Cohort Study (UKWCS). Issue 4 (1st April 2018) - Rada‐Fernandez de Jauregui, Diego; Evans, Charlotte E.L.; Jones, Petra; Greenwood, Darren C.; Hancock, Neil; Cade, Janet E.
Abstract : Few prospective cohort studies in the UK have specifically focused on the associations between commonly consumed dietary patterns and colorectal cancer (CRC). The aim of our study was to assess whether red meat, poultry, fish and vegetarian dietary patterns are associated with differences in the incidence of cancers of colon and rectum in the UKWCS. Four common dietary patterns were defined based on a hierarchy of consumption of red meat, poultry and fish for each cohort participant, using a 217‐item food frequency questionnaire. Cox proportional hazards regression was used to provide adjusted hazard ratios (HR) and 95% confidence intervals (CI) for CRC. A total of 32, 147 women recruited and surveyed between 1995 and 1998 were followed up for a mean of 17.2 years (426, 798 person‐years). A total of 462 incident CRC cases were documented; 335 colon cancers (172 proximal and 119 distal) and 152 in the rectum. In multivariable‐adjusted models, there was no evidence of a reduction in risk of overall CRC (HR = 0.86, 95% CI: 0.66–1.12), colon cancer (HR = 0.77, 95% CI: 0.56–1.05) or rectal cancer (HR = 1.04, 95% CI: 0.66–1.63) when comparing grouped red meat free diets with diets containing red meat. Exploratory analysis suggested a reduced risk of distal colon cancer in grouped red meat free diets (HR = 0.56, 95% CI: 0.34–0.95), though numbers with this outcome were small. These results indicate that a protective association of red meat free diets specifically on distal colon cancer merits confirmation in a larger study. Abstract : What's new? Eating red meat may affect one's risk of colon cancer. Here, the authors looked for a relationship between colorectal cancer risk and red meat, poultry, fish, and vegetarian diets. They used data from the UK Womens Cohort study, with dietary information collected by survey. No statistically significant association was found for total CRC risk, but when they looked at specific cancer sub‐sites, a correlation emerged. Although numbers were small, a reduction in distal CRC risk was observed among those who did not eat red meat. A larger study would be desirable to confirm these findings.